Concentrations of Heavy Metals in the Soft Tissues of Mudflat Snails (Telescopium Telescopium) From the Intertidal Areas of Peninsular Malaysia - Arifin, Noorhaidah (2008)
The main aim of this study is to establish mudflat snail Telescopium telescopium as a biomonitor of heavy metals for the intertidal area of Peninsular Malaysia. From this study, the concentrations of heavy metals in the different parts of soft tissues and shells were determined in T. telescopium collected from 16 geographical sites along the west coast and one site from the east coast (Tumpat, Kelantan) of Peninsular Malaysia. Based on the 17 populations, the mean concentrations of heavy metals in the total soft tissues of T. telescopium varied widely from 53.59 – 187.07 μg/g dry weight for Cu, 65.11 – 155.38 μg/g dry weight for Zn, 5.59 – 17.66 μg/g dry weight for Pb, 0.40 – 1.52 μg/g dry weight for Cd, 4.63 – 17.29 μg/g dry weight for Ni and 304.06 – 1062.19 μg/g dry weight for Fe. The soft tissues of snail T. telescopium were dissected, separated and pooled into seven parts namely foot, cephalic tentacle, mantle, muscle, gill, remaining soft tissues and digestive caecum and the concentrations of heavy metals in these tissues were measured. In the study of the relationship between different soft tissues of T. telescopium with its environment represented by sediment samples, the Pearson’s correlation coefficients results showed positive significant correlation (p< 0.05) were observed between Cd, Cu, Fe, Ni, Pb and Zn in the different soft tissues and geochemical fraction of 6 metals studied in the sediment. The Pearson correlation coefficients suggested that some soft tissues can be good biomonitoring organs (Cu: mantle and remaining soft tissues; Fe: mantle, remaining soft tissues and foot; Ni: gill and remaining soft tissues; Pb: gill, remaining soft tissues and digestive caecum; Zn: gill and remaining soft tissues). It is noted that particular organ may be more effective tool than the total soft tissues to monitor heavy metal contamination in the intertidal zone. The study on the ratio of metals in the shell to the metals in the different soft tissues shows that shell has higher degrees of variability for Cd, Ni and Pb than in the different soft tissues of T. telescopium. Therefore, the results indicated lower degrees of variability of Fe, Cu and Zn in the shells of T. telescopium than in the different soft tissues of T. telescopium. In conclusion, the metal distributions in the different soft tissues of T. telescopium indicated that a particular organ is more useful and accurate to monitor a particular metal contaminations in the intertidal area. The shells and soft tissues of T. telescopium are found as potential biomonitor of Cd, Cu, Fe, Ni, Pb and Zn while the usefulness of the shells need further studies.